Analisis Implementasi Praktikum Kimia Kelas XI SMA Negeri di Kabupaten Gowa - Mutmainnah, Nurul; Anwar, Muhammad; Syahrir, Muhammad (Chemistry Education Review (CER), 2024)
This study aims to analyze the implementation of Chemistry practicum of grade XI at SMAN in Gowa Regency. The method used is descriptive method with a quantitative approach. The study was conducted at all public high schools in Gowa Regency. The objects were the school’s principals, Chemistry teachers, and all grade XI MIPA students. Determination of the sample employed porposive sampling technique which was based on certain characteristics (schools accredited A, B, and C). Data collection techniques employed observation sheets, questionnaires, interviews, and documentation. The results of the study reveal that the average percentage of the availability of tools and materials to support the practicum implementation is 69%, which is in Appropriate category, while the implementation of Chemistry practicum seen from the average percentage of teachers’ response questionnaires is 84% which is in Very Good category, and the average percentage of the students’ response questionnaires is 80% which is in Good category. The result of the interviews can be concluded that the biggest obstacle to practicum implementation is the lack of availability of practicum tools and materials. The analysis results of the syllabus and lesson plans show that there are ten main subject materials for learning Chemistry. Nine of those main subject materials require practicum activities.